Life cycle assessment for a solar energy system based on reuse components for developing countries. (20th January 2019) - Kim, Bunthern; Azzaro-Pantel, Catherine; Pietrzak-David, Maria; Maussion, Pascal
Abstract: In many developing countries, the lack of electricity in rural areas is still a key issue for millions of people. The reuse of discarded components in renewable energy systems, based on the frugal innovation concept, has been identified as a solution for rural electrification in countries where renewable resource is plentiful. Specific emphasis is paid in this work to the application of reuse from an engineering viewpoint for a Renewable Energy System, including a "solar" element, composed of solar Photovoltaic (PV) panels and of modified Power Supply Units (PSUs), a "hydro" part and an energy storage system with used car batteries. The scientific objective of this work is to evaluate the environmental impact of this solution, considering only the solar element, as compared to a conventional system consisting of photovoltaic panels, lead-acid batteries, a charge controller and an inverter for small village consumption. For this purpose, Life Cycle Assessment (LCA) has been selected as a methodological framework and both solutions have been described and sized. The results have shown that in the reuse scenario, the impact of PSUs, Uninterruptable Power Supply Units (UPSs) and a microcontroller kit remains very low (0.12% of total impact) while PV modules contribute significantly (66% of total impact). Nevertheless, the consequences of reusing lead-acid batteries are still significant due to the combination of several effects: their weight, reduced efficiency and the need for frequent replacement. A 40% reduction of the environmental burden obtained by the reuse solution is clearly due to the absence of battery production impacts in the case of reuse. A sensitivity analysis has been performed to determine the impact of parameters such as component efficiency, lifetime and transportation distance on environmental impacts. The efficiency of repurposed PSUs and UPSs is the most significant parameter on the environmental impact categories in the reuse solution.